KARAKTERISTIK IBU BERDASARKAN PENGGUNAAN ALAT PERMAINAN EDUKATIF (APE) UNTUK MENSTIMULASI ANAK PRA SEKOLAH - Erien Luthfia; Hadi Kusuma Atmaja (Jurnal Penelitian, 2020)
Pre school period is the beginning of the development of physical abilities, cognitive, language, social emotional, self-concept, discipline, independence, art, morals, and religious values. Therefore, so that the child's growth and development can be optimally needed and stimulation that suits the child's needs, can be done by the mother. A preliminary study conducted in the Sandik, Batu Layar, Lombok Barat, NTB about the use of educational play instruments by interviewing 10 mothers, the results obtained, 7 mothers provided educational play tools for users by using tools and benefits of play tools. APE to stimulate pre school children in 2019.The research design is descriptive method. The population in this study is mothers who have pre-school children. The sampling technique is saturated sampling with a large sample of 45 people. Data collection using questionnaires.The results showed that the most respondents were aged 20-35 years (71.1%), had secondary education (SMP / SMA / equivalent) as much as 64.4%, and as many as 66.7% of respondents were working mothers. Knowledge of respondents in the good category was 64.4%. The conclusion of this study is that the characteristics of respondents who use APE to stimulate pre-school children are aged 20-35 years, have secondary education, work, and have a good level of knowledge. For this reason, mothers should continue to improve their knowledge of educational game tools through the correct sources of information.